Developing Endogenous Innovations: Corporate Entrepreneurship and Effectuation - Parker, J; Corner, PD; Woodfield, PJ; Singh, S (Walter de Gruyter GmbH, 2019)
We empirically explore the process of corporate entrepreneurship (CE) through the conceptual lens of effectuation, a theory describing how entrepreneurs innovate. In particular, we investigate how endogenous innovations emerge and evolve into new products or services. The study thus provides an alternative perspective to most CE research that assumes a causation or rational-analytic approach to innovation. We implement a qualitative, multi-case study research design with corporate innovation projects as the level of analysis. Data are from interviews as well as secondary sources and were analyzed using within and cross case analysis. Findings reveal organic stages through which ideas are shaped into viable products. Findings show important effectuation principles at work including stakeholder commitments, affordable loss thinking, and a focus on control instead of prediction. Interestingly, findings illustrate how effectuation may differ in the corporate as compared to the new venture context. Implications for the wider literature are discussed along with limitations of the research design.
Keywords: Effectuation; Corporate entrepreneurship; Innovation process; Product development; Qualitative research design